STRUKTUR PENYAJIAN TARI RADAT KAMI PEMUDA ISLAM INDONESIA DI DESA BEKUT - Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the lack of writing or documenting traditional dance in the Sambas district which almost suffered extinction. One of them is the traditional dance that has almost suffered extinction, is The Structure of We are Indonesian Youth Islamic Radat Dance in Bekut Village, Tebas District, Sambas Regency, West Kalimantan. The objectives of this research are as follows 1). Descriptions of the structure of the presentation ofÂ The Structure of We are Indonesian Youth Islamic Radat Dance in Bekut Village, Tebas District, Sambas Regency. 2). Descriptions of supporting elements on The Structure of We are Indonesian Youth Islamic Radat Dance in Bekut Village, Tebas District, Sambas Regency. The method used is descriptive analysis with a qualitative form. The approach used is the Ethochoreology approach. Data sources are divided into two, namely primary data and secondary data. Data collection techniques in the form of interview techniques, observation techniques, and documentation techniques. Techniques for collecting data from researchers as instruments. The technique of testing the validity of the data is the technique of extension of observation and triangulation techniques. The data analysis technique used is, analyzing and interpreting the history of development, the structure of the presentation of motion, the design of the implementation of the school regarding the history of We are Indonesian Youth Islamic Radat Dance.Â Keywords: Dance Moves, Exploration, Role Playing Method